NICE SYSTEMS: NICE signs definitive agreement with IBS Corporation (M2 Presswire, 1998)
M2 PRESSWIRE-3 March 1998-NICE SYSTEMS: NICE signs definitive agreement with IBS Corporation (C)1994-98 M2 COMMUNICATIONS LTD NICE Systems Ltd. (NASDAQ:NICEY) today announced it has signed a definitive agreement, subject to closing, to acquire the assets of IBS Corporation, a privately held software company based in San Diego, as part of its strategy to become the dominant player in the call centre logging and quality market. With IBS's base of call centre technologies, NICE increases its suite of quality offerings for the call centre market. The agreement enables NICE to improve its offering for large corporations with multiple call centres in various locations and to address the IBM Mainframe market, providing high-end, fully integrated voice-and-screen monitoring and coaching together with quality tracking.